Amy & Lan : a novel - Jones, Sadie (Harper, an imprint of HarperCollinsPublishers, 2022)
"Amy Connell and Lan Honey are having the best childhood, growing up on a West Country farm--with three families, a couple of lodgers, goats, dogs, and an orphaned calf called Gabriella Christmas. The parents are best friends, too. Originally from the city, they're learning about farming: growing their own vegetables, milking the goats, slaughtering chickens, and scything the hay-- "Mind your eyes! Careful, that's sharp! Don't break your neck!" The grown-ups are far too busy to keep an eye on the children, and Amy and Lan would never tell them about climbing on the high barn roof, or what happened with the axe that time, any more than their parents would tell them the things they get up to--adult things, like betrayal--that threaten to bring the whole fragile idyll tumbling down."--Dust jacket flap.